Leverage dan Kinerja Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Ni Putu Budiadnyani; Putu Pande R. Aprilyani Dewi; I G A Desy Arlita (Politeknik Ganesha Medan, 2023)
Companies are generally established with the aim of making a profit. The company's operational activities cannot be separated from the use of external funds to support the company's activities. This study examines the effect of leverage on financial performance. In addition, this study also examines the ability of firm size as a moderating variable. This research is expected to contribute to management to consider the size of the company owned so that it is effective in improving company performance. The number of samples analyzed was 54 samples in the form of financial reports from banking sector companies listed on the Indonesia Stock Exchange. The sampling technique in this study is the non-probability sampling method with a purposive sampling technique with the criteria of companies (issuers) that have issued financial reports consecutively for the 2019-2021 period and companies (issuers) that have not suffered losses during the 2019-2021 period. The analysis technique used is simple linear regression and Moderated Regression Analysis (MRA). The results of the analysis show that leverage has no effect on company performance. Firm size weakens the effect of leverage on firm performance.